2013
DOI: 10.1111/jen.12041
|View full text |Cite
|
Sign up to set email alerts
|

A rapid diagnostic tool for two species of Tetradacus (Diptera: Tephritidae: Bactrocera) based on species‐specific PCR

Abstract: Bactrocera minax and Bactrocera tsuneonis are two sibling species of the Bactrocera subgenus Tetradacus with significant quarantine importance in Asia. It is difficult to identify or distinguish them only based on morphological characteristics. In this study, microscopic observations showed that morphological features of adult samples were congruent with the diagnosis of the two species. In this study, we describe species-specific PCR for the molecular identification of B. minax and B. tsuneonis. Species-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…The methods of sample preservation, DNA extraction, COI gene amplification (/) and sequencing were reported previously by Jiang et al . (,b). We used Chromas 1.45 (McCarthy ) to review the sequencing results, and bidirectional sequences were assembled for each specimen using the dnaman 5.2.2.0 software (Lynnon Corporation, Quebec, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…The methods of sample preservation, DNA extraction, COI gene amplification (/) and sequencing were reported previously by Jiang et al . (,b). We used Chromas 1.45 (McCarthy ) to review the sequencing results, and bidirectional sequences were assembled for each specimen using the dnaman 5.2.2.0 software (Lynnon Corporation, Quebec, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, researchers collected the fruit fly samples only in Guizhou, Sichuan and Hunan provinces. Jiang et al only obtained three DNA barcode sequences from B. minax and two DNA barcode sequences from B. tsuneonis [37]. In this case, more reliable species-specific primers were successfully redesigned based on DNA barcode sequences obtained from 963 individuals and download from GenBank with the highest abundance possible, which almost covered all distribution spots of B. minax and B. tsuneonis in China.…”
Section: Species-specific Primer Selection Specificity Test and Sensmentioning
confidence: 99%
“…Asokan et al (2011) designed species-specific primers based on DNA barcode sequences to establish a method for B. dorsalis and B. zonata identification, and this method could reliably identify all life stages of the target species [36]. It is worth noting that in 2014, Jiang et al designed species-specific primers of B. minax and B. tsuneonis based on the DNA barcoding sequences from Guizhou, Sichuan and Hunan Provinces [37]. We found false-positive results when we used these primers for the identification of the two Tetradacus species collected from Guizhou, Sichuan, Yunnan, Hubei, and Chongqing Provinces or city areas, which were not involved in the previous study.…”
mentioning
confidence: 99%
“…; Jiang et al. ). Thus, we were interested in matching DNA barcodes with morphologically identified B .…”
Section: Introductionmentioning
confidence: 98%
“…Previous taxonomic study reported that male B. ocellaris from the Australian region have differences in the ratio of antennal segments compared to males from other zoogeographic regions, even though the genital structure is within the range of intraspecific variation (Menzel et al 2003). In such cases, molecular identification can be helpful for identification of the species complex (Hebert et al 2004a;Smith et al 2007;Burns et al 2008;Rivera and Currie 2009;Naaum et al 2012Naaum et al , 2014Kumar et al 2013;Jiang et al 2014). Thus, we were interested in matching DNA barcodes with morphologically identified B. ocellaris male specimens.…”
Section: Introductionmentioning
confidence: 99%